The effect of training, discipline, and motivation on employee performance - Esthi, Raniasari Bimanti (FORUM EKONOMI, 2021)
Competition in the business world today is increasing, which causes every company to try to achieve a higher competitive advantage than its competitors. The problem in this study is whether training, discipline, and work motivation affect the performance of employees. The purpose of this study is (1) to determine the effect of partial training on employee performance, (2) to determine the effect of partial discipline on employee performance, and (3) to determine the partial effect of work motivation on employee performance. Questionnaires were distributed to 53 respondents using simple random sampling method. The total population is 170 employees. The designated population is the production and quality employees of PT. Nippon Steel Chemical and Materials Indonesia. The questionnaire data was processed using multiple regression analysis with the results showing that (1) training has an effect on employee performance, (2) there is a significant effect of discipline on employee performance, and (3) and work motivation has an effect on employee performance.